Study on the polymorphism of methylenetetrahydrofolate reductase C677T gene as the genetic predisposition of congenital heart disease in North Indian population - Panja, Amrita; Abhinay, Abhishek; Pakhira, Antim Akash (Asian Journal of Medical Sciences, 2022)
Background: The etiology of congenital heart disease (CHD) is still not known properly. The variant alleles in the methylenetetrahydrofolate reductase (MTHFR) C677T gene help in elevating the serum homocysteine level which is an independent predisposing factor for generating CHD. Aims and Objectives: The aim of the present study was to analyze the role of polymorphism of MTHFR C677T gene polymorphisms in CHD patients of Varanasi, Uttar Pradesh, North India. Materials and Methods: The present study included 36 unrelated CHD patients along with their parents. At the same time, 40 healthy control samples were included in the study. MTHFR 677 C>T genotype was identified by polymerase chain reaction followed by restriction digestion restriction fragment length polymorphism mechanism. Results: There was a significant difference observed in MTHFR C677T gene polymorphism between the cases and controls (P<0.001). Among the different etiological factors, increased maternal age, family history, and teratogens are the major ones. Maternal MTHFR C677T genotype and periconceptional folate intake have important ascription toward CHD formation. Conclusion: The results designate that MTHFR C677T polymorphism has a substantial association with the development and progression of CHDs. Folate supplementation might be the probable management strategy for reducing the risk of CHDs as maternal MTHFR C677T polymorphism has an important contribution.